TEACHING PASSIVE VOICE IN EFL CLASSROOM THROUGH THE IMPLEMENTATION OF ICT - Fitri, Lini (Jurnal Ilmiah Spectral, 2018)
Teaching English Grammar is not easy because there are several factors causing the lack of motivation and concentration of the learner in acquiring the grammar-based inputs of the English language in the classroom. In language teaching, teachers need to understand how to make the classroom as a place of learning and not just a classroom for the students to learn during the teachingprocess. With the rapid growth of technology language teachers can select the tools that appropriate with the teaching objective. The application of Information and Communication Technology (ICT), particularly educational software, to facilitate the learning and teaching process has become a more and more popular trend among teachers. Therefore, this study attempts to highlight teaching passive voice in the EFL Classroom through the implementation of ICT in teaching and learning process.